Bugis ethnomathematics: Exploration of the sulapa eppa walasuji motif as a source of learning mathematics - Aras, Andi; Nasruddin; Zahrawati B., Fawziah; Syahrul (Jurnal Elemen, 2025)
Mathematics has historically been integrated into everyday life, and Indonesia's cultural heritage, such as the walasuji of the Bugis community, provides a valuable context for learning. This study explores activities involving mathematical concepts found in the making of walasuji. A descriptive qualitative method with an ethnographic approach was used. Data were collected through observation, documentation, and interviews. The findings reveal that making walasuji involves mathematical concepts such as translation, reflection, rotation, and straight-line equations, offering potential as contextual learning resources in schools. Additionally, the sulapa eppa walasuji motif embodies character values manifested in humans, namely intellectuality (acca), courage (warani), honesty (lempu), and wealth (sugi), referred to as sulapa eppa na taue (the philosophy of a quadrilateral human). Integrating cultural artifacts like walasuji into mathematics learning can enhance students' engagement, cultural awareness, and critical thinking skills. This research implies that future mathematics education should incorporate elements of local wisdom to create meaningful, relevant, and culturally responsive learning experiences, aligning mathematics more closely with students' everyday realities and cultural identities.